Unusual Bilateral Paramolars Associated with Clinical Complications - A. N. Sulabha; C. Sameer (Case Reports in Dentistry)
Paramolars are rare supernumerary structures of maxillofacial complex that occur buccally or lingually near the molar row. Predominantly these occur singly; bilateral presentation is very rare. This paper reports two unusual bilateral presentations of paramolars with clinical complication and its management. One of the cases in the present paper also documents the cooccurrence of bilateral paramolars and microdontia of single tooth and one of its paramolars presented with multilobed crown with an anomalous buccal tubercle.